2020
DOI: 10.1177/0890117119895951
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Healthy Eating Interventions in Center-Based Childcare: The Selection, Application, and Reporting of Theories, Models, and Frameworks

Abstract: Purpose: To explore the selection, use, and reporting of theories, models, and frameworks (TMFs) in implementation studies that promoted healthy eating in center-based childcare. Data Source: We searched 11 databases for articles published between January 1990 and October 2018. We also conducted a hand search of studies and consulted subject matter experts. Study Inclusion and Exclusion Criteria: We included studies in center-based settings for preschoolers that addressed the development, delivery, or evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 87 publications
(113 reference statements)
0
7
1
Order By: Relevance
“…A strength of this study is the eligibility criteria, which facilitated the large number of eligible articles relative to pre-existent bibliometric studies of TMF applications in implementation research ( 20 22 ). The study also summarizes TMF applications in clinical AI research, a prominent and growing category of digital health implementation research which had not yet been subject to any similar bibliometric studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strength of this study is the eligibility criteria, which facilitated the large number of eligible articles relative to pre-existent bibliometric studies of TMF applications in implementation research ( 20 22 ). The study also summarizes TMF applications in clinical AI research, a prominent and growing category of digital health implementation research which had not yet been subject to any similar bibliometric studies.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation research focused on other categories of healthcare interventions has been characterized through descriptive summaries of TMF selection and usage. These studies act as a frame of reference, but to our knowledge none report on digital health interventions ( 20 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a systematic review of school-based physical activity and sedentary behaviour interventions, Cassar [ 51 ] reported three of 14 included studies used the RE-AIM framework. A review specific to TMFs within childcare settings identified RE-AIM was used in evaluation of two of the 38 included studies [ 52 ]. Traditionally, RE-AIM is an implementation evaluation framework used to identify and evaluate aspects of the implementation process [ 53 ] and as such, provides essential guidance to the success of implementation strategies and potentially intervention outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, users of this review should be aware of the commonly acknowledged challenge that implementation studies may not always build on standard criteria for quality reporting of findings. While such standards exist (Pinnock et al, 2017a(Pinnock et al, , 2017b, their widespread use is still pending and insufficient reporting of, for example, implementation interventions or contextual factors, remains a persistent issue (Vale et al, 2020;Wilson et al, 2017) that also may characterize the studies included in this review. Hence, the findings presented here reflect what was reported in included studies and may therefore be incomplete.…”
Section: Discussion and Applications To Practicementioning
confidence: 99%